FEATURES OF REGIONAL DEVELOPMENT IN MODERN CONDITIONS - Кульчицька, Надія; Дерманська, Людмила (SWorldJournal, 2024)
The article examines the importance of stimulating regional development in today’s complex political, economic and social conditions. In particular, an analysis of the implementation of the regional budget of the Ternopil region was carried out, the dyna